Efektivitas Penggunaan Daun Kembang Sepatu sebagai Agensia Defaunasi dalam Pakan Berkonsentrat Tinggi dengan Jenis Hijauan Berbeda Ditinjau dari Kecernaan Nutrienpada Kambing Kacang Jantan - Susi Dwi Widyawati; Siska Frimadani Silalahi; Isti Astuti (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2017)
Feeding high-concentrateration stimulates the protozoa to grow quickly, thus inhibits the growth of rumen bacteria,and leads to decrease in digestibility of nutrients, especially crude fiber. Defaunation is required to reduce the protozoa population in the rumen, for exampleby using China rose (Hibiscus rosa-sinensis) leafwhich containing saponins. This study investigated the effectiveness of China rose leaf as defaunation agent in high-concentrate feed with different forage based on nutrient digestibility in kacang goats. A total of16 male kacang goats with average body weight of 13.68 ± 1.55 kg was divided into 2 treatments i.e. P1: 40% peanut straw + 50% concentrate + 10% China roseleaf and P2: 40% king grass + 50% concentrate + 10% China rose leaf. The data obtained were analyzed by t-test. The results showed that the goats fed peanut straw generated higher (P<0.05) dry matter intake than the goats fed king grass (819.56 vs 678.65 gram/head/day). Furthermore, the dry matter digestibility in goats fed peanut straw was higher (P<0.01) than king grass (81.93 vs71.64%). The same results were observed for the digestibility of organic matter (82.96 vs74.35%) and crude fiber(78.12 vs 64.00%). It can be concluded that the use of China roseleaf in ration containing peanut strawwas more effective as defaunation agent as indicated by higher nutrient digestibility rather than in ration containing king grass.